Carbon allocation to the root system of tropical tree Ceiba pentandra using 13C pulse labelling in an aeroponic facility. (24th January 2020) - Mannerheim, Neringa; Blessing, Carola H; Oren, Israel; Grünzweig, José M; Bachofen, Christoph; Buchmann, Nina
Abstract: Despite the important role of tropical forest ecosystems in the uptake and storage of atmospheric carbon dioxide (CO2 ), the carbon (C) dynamics of tropical tree species remains poorly understood, especially regarding belowground roots. This study assessed the allocation of newly assimilated C in the fast-growing pioneer tropical tree species Ceiba pentandra (L.), with a special focus on different root categories. During a 5-day pulse-labelling experiment, 9-month-old (~3.5-m-tall) saplings were labelled with 13 CO2 in a large-scale aeroponic facility, which allowed tracing the label in bulk biomass and in non-structural carbohydrates (sugars and starch) as well as respiratory CO2 from the canopy to the root system, including both woody and non-woody roots. A combined logistic and exponential model was used to evaluate 13 C mean transfer time and mean residence time (MRT) to the root systems. We found 13 C in the root phloem as early as 2 h after the labelling, indicating a mean C transfer velocity of 2.4 ± 0.1 m h −1 . Five days after pulse labelling, 27% of the tracers taken up by the trees were found in the leaves and 13% were recovered in the woody tissue of the trunk, 6% in the bark and 2% in the root systems, while 52% were lost, most likely by respiration and exudation. Larger amounts of 13 C were found in root sugars than in starch, the former also demonstrating shorter MRT than starch. Of all investigated root categories, non-woody white roots (NRW ) showed the largest 13 C enrichment and peaked in the deepest NRW (2–3.5 m) as early as 24 ± 2 h after labelling. In contrast to coarse woody brown roots, the sink strength of NRW increased with root depth. The findings of this study improve the understanding of C allocation in young tropical trees and provide unique insights into the changing contributions of woody and non-woody roots to C sink strengths with depth.